Altered miRNA expression in the cervix during pregnancy associated with lead and mercury exposure. (September 2015) - Sanders, Alison P; Burris, Heather H; Just, Allan C; Motta, Valeria; Amarasiriwardena, Chitra; Svensson, Katherine; Oken, Emily; Solano-Gonzalez, Maritsa; Mercado-Garcia, Adriana; Pantic, Ivan; Schwartz, Joel; Tellez-Rojo, Martha M; et al.
Aim: Toxic metals including lead and mercury are associated with adverse pregnancy outcomes. This study aimed to assess the association between miRNA expression in the cervix during pregnancy with lead and mercury levels.Materials & methods: We obtained cervical swabs from pregnant women (n = 60) and quantified cervical miRNA expression. Women's blood lead, bone lead and toenail mercury levels were analyzed. We performed linear regression to examine the association between metal levels and expression of 74 miRNAs adjusting for covariates.Results: Seventeen miRNAs were negatively associated with toenail mercury levels, and tibial bone lead levels were associated with decreased expression of miR-575 and miR-4286.Conclusion: The findings highlight miRNAs in the human cervix as novel responders to maternal chemical exposure during pregnancy.